(untitled) (Research, Society and Development, 2022)
The production of food in diverse spaces is on the rise, whether for own consumption or for commerce, also meeting the growing interest of the population in growing their own food. Strawberry is a widely consumed food and considering its importance to society, the construction of greenhouses for its semi-hydroponic (SH) cultivation in a low tunnel (TB) in a small area was evaluated, combining the advantages of the off-ground system. and protected to ergonomic conditions, with materials of easy access and low cost. A bibliographic study was carried out to evaluate the advantages and disadvantages of each strawberry production system. After defining the system to be implemented, three 3 m x 1 m greenhouses were built in the external area of ​​the State University of Rio Grande do Sul (UERGS), with benches at 0.80 m from the ground and a low tunnel cover at 0.70 m from the bench, for the cultivation of 48 strawberry plants. For the development of the culture, the pre-formulated fertigation system was chosen. After 60 days of transplantation, the plants were producing strawberries and, in the months of June to October of the year following the implantation, the peak of production was reached, demonstrating the efficiency of the new proposed structure for the cultivation of strawberries.